Upregulated lnc-HRK-2:1 prompts nucleus pulposus cell senescence in intervertebral disc degeneration - Liang, Dongbo (Mol Med Rep, 2020)
Intervertebral disc (IVD) degeneration is a complicated physiological change involving cellular senescence, inflammation and the degradation of the extracellular matrix. Long non-coding RNAs (lncRNAs) have been identified as new players in IVD degeneration. The present study aimed to identify lncRNAs implicated in IVD degeneration via the regulation of cellular senescence. In the present study, nucleus pulposus (NP) cells isolated from moderately degenerated IVD tissues exhibited a senescent phenotype with increased senescence rates, detected by senescence-associated β-galactosidase (SA-β-gal) staining, and reduced growth and migratory abilities. Microarray and target prediction analyses identified 353 differentially expressed lncRNAs, and 251 cis- and 2,170 trans-acting targets in degenerated NP cells. Bioinformatic analyses revealed that these predicted targets were enriched in the regulation of response to DNA damage stimulus, positive regulation of cell cycle processes and interferon-β production. In addition, a network of the top 10 upregulated and top 10 downregulated lncRNA targets was constructed, and two trans-acting targets, C-C motif chemokine ligand 5 (CCL5) and polyribonucleotide nucleotidyltransferase 1 (PNPT1) involved in aging or senescence, and their corresponding lncRNAs, lnc-ST8SIA5-1:2 and lnc-HRK-2:1, were identified. Reverse transcription-quantitative PCR validation demonstrated that the two targets and two candidate lncRNAs were significantly upregulated in degenerated NP cells. Overexpression of lnc-HRK-2:1, with validated higher expression levels, in normal NP cells induced a senescent phenotype, with enhanced rates of senescence detected by SA-β-gal staining in cells, decreased growth and migratory abilities and improved expression levels of CCL5 and PNPT1. Collectively, these results suggested that upregulation of lnc-HRK-2:1 prompted NP cell senescence in IVD degeneration, which may be associated with increased expression levels of CCL5 and PNPT1.